Transformation of the content in music compositions as a factor of actualization of precedent phenomena («Anthem /The Eternal Revolutionary/» by Ivan Franko — Mykola Lysenko) - Siuta, Bogdan (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
The relevance of the study. The perception and understanding of works of culture and art, the formation of their contents continue to be one of the most pressing issues of the functioning of artistic culture in society. This is due to a significant number of reasons, among which several demonstrative ones stand out. First of all, let’s mention the significant complexity of language and expressive means used by composers during the 19th-21st centuries. We also consider the insufficient cultural competence of a significant number of readers/listeners to be the effective reason, caused primarily by the lack of experience in perceiving complex works of art. We should also note the forward-looking guidance on the availability of averaged contents and the clarity of meanings when perceiving works of art. A purposeful study of the process of forming the contents of prescribed works of art requires a careful study of the status of the precedents involved in it. The problem of studying the peculiarities of such mechanisms of perception and understanding of art, used by authors and interpreters, is also minimally developed and requires a thorough understanding and rethinking. In our opinion, the solution of these questions is also important for a whole group of humanitarian sciences, which use paramusical and cross-cultural realities in the processing. A number of important issues of such processing actually became the subject of our consideration. The main objective of the study is to us the example of the musical piece "Anthem (The Eternal Revolutionary)" by Ivan Franko - Mykola Lysenko to find out the implicit or hidden sources of content creation in musical works, the subject of which is based on the use of a wide field of socio-cultural realities; to reveal reactualized precedent phenomena in the song, which, on the one hand, enrich the content resource of the work, and, on the other hand, are the main reason for the transformation and change of its original contents. The methodology uses source studies and biographical methods (to clarify the involved facts and cultural-historical context), stylistic method (to highlight the peculiarities of creative priorities, style and content creation in the works of I. Franko, J. Słowacki, and M. Lysenko), as well as structural-functional method and method of precedent analysis. Results and conclusions. The issue of content transformation as a manifestation of the precedent nature of musical works has been investigated. It has been proven that content changes are mostly the result of many reasons. These primarily include: 1) the complexity of the language and expressive means used in the work; 2) insufficient cultural competence and ignorance of the recipient; 3) guidance on the recipient’s accessibility of basic contents and clarity of meanings when perceiving works of art; 4) superficial acquaintance of the recipient with the ideological and artistic content and "approximate" awareness of it; 5) purposeful influence on the recipient of factors of ideological influence. On the material of the song "Anthem (The Eternal Revolutionary)" by I. Franko - M. Lysenko, the status of precedent phenomena actualized when perceiving the work has been characterized in detail - names, situations, texts. For this purpose, a number of source studies, historical, socio-worldview and semantic discourses of an interdisciplinary and cross-cultural nature have been involved. The importance of taking into account the transformation of contents as a result of historical and socio-cultural changes has been demonstrated, the necessity of adjusting the processes of content creation in view of such transformations has been proved. The influence on the perception of the works of involuntary misconceptions about certain historical realities of a sociocultural nature has been also shown ("The Eternal Revolutionary" is somehow related to the October revolution in Russia; "peaks and lowlands" are elements of the Carpathian mountain landscape; Ivan Franko was an atheist; the expression "The Eternal Revolutionary" belongs to I. Franko; the Spirit is an emotionally marked mood of certain groups of people, and not a higher divine power originating from Jesus and the Holy Trinity, etc.). The effective possibilities of musical and expressive means to strengthen / weaken the degree of emotional saturation of values, to change and reformat them, bringing to the fore primary precedents, has been proved.